Meningkatkan Prestasi Belajar Pendidikan Agama Islam Melalui Media Video Pada Siswa Kelas V SDN Gentong 1, Kecamatan Paron, Kabupaten Ngawi Tahun Pelajaran 2016/2017 - Muhammad Abduh; Rido Kurnianto; Nurul Abidin (Universitas Muhammadiyah Ponorogo, 2018)
To achieve a pleasure Islamic Education learning which is fancied by primary students, researcher used video as a media in students learning material, so there is an innovation.The aims are to give a comfortable and happy feeling in Islamic Education learning process and to increase students’ academic achievement. Researcher used Classroom Action Research for this study. The subjects for this research were 20 students of Fifth Grade in Gentong 1 Primary School. The research design used Kammis and Taggar model which is through planning, action, observation and reflection process. The used instruments were classroom observation sheet and test questions sheet. Data collection technique was done by observation, test, interview and documentation. And the data analysis was done by using quantitative description. The result of this study proved that there is an enhancement in Islamic Education learning achievement on fifth grade students of Gentong 1 Primary School through video as the media. Based on the collected data from pre-observation 68.50 (60%), after the observation at Cycle I became 70.75 (80%), at Cycle II became 70.75 (70%), and after Cycle III became 77.5 (80%). The increasing students’ learning achievement through video as the media was supported by some factors such as innovation, method and students’ learning motivation.